The relationship between teachers’ power perception, teachers’ perception of child, and child-teacher interaction - Cabi, Nehir. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The main purpose of this study was to analyze the teachers’ perceptions of child, power and their interactions with children. The issues of power, discipline, authority, and the concepts of school, teacher and child were used to examine teachers’ comprehensions of the culture of power in classroom. The sample of the study was four female primary school teachers in a public school in Istanbul, Turkey. The results showed that there was a relational sphere between power and child perceptions of the teachers. The teachers’ perceptions of authority and discipline embedded to the conceptions of child and school context. The teachers’ perceptions of authority and discipline embedded to the conceptions of child and school context. In addition to this, teachers’ child and power perceptions reflected to teacher-child relationship as a shortcut of and nonverbal communication in classroom. Findings suggest that teachers’ explanations about power and child concepts are fed each other by the same concern that is the anxiety of losing their control of power over children. The findings of the current study provide to analyze the internalization and externalization process of power, child and their effects on teacher-child interaction in educational arena.
Keywords: Teacher-principal relationships.; School discipline.; Classroom management.